Production of dammarane-type sapogenins in rice by expressing the dammarenediol-II synthase gene from Panax ginseng C.A. Mey - Huang, Zhiwei (Plant science : an international journal of experimental plant biology, 2015)
Copyright © 2015 Elsevier Ireland Ltd. All rights reserved.